STRATEGI DINAS PERIKANAN KABUPATEN ROKAN HILIR DALAM PELAKSANAAN PENYALURAN BANTUAN KEPADA NELAYAN TANGKAP TAHUN 2016-2020 - Melisa Saptiona; Khairul Anwar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Distribution of assistance to fishermen in an area has an important role in meeting the needs, development, maintenance and improvement of the economy and welfare of the fishing community. The management of capture fisheries development in Rokan Hilir Regency is under the Fisheries Service, which means that there is a need for a strategy for the Rokan Hilir Regency Fisheries Service regarding the phenomenon that the distribution of aid is not right on target, and capture fisheries production has increased and decreased which is also a challenge as well as an opportunity for the Department of Fisheries and Fisheries. fishing community.This study aims to determine the strategy of the Fisheries Service of Rokan Regency in the implementation of distribution of assistance to fishermen and what are the inhibiting factors in the implementation of distribution of assistance to fishermen in 2016-2020. This study uses a qualitative approach with a descriptive method. In collecting data, the author uses interview and documentation techniques.The results of this study indicate that the strategies of the Fisheries Service of Rokan Hilir Regency are socialization to fishermen, auxiliary fisheries counseling, supervision of the implementation of aid distribution and evaluation of the implementation of aid distribution. The strategy carried out by the Fisheries Service of Rokan Hilir Regency was not optimal because there were recipients of assistance who were not on target. The inhibiting factor in the implementation of the distribution of assistance to fishermen is internal constraints (government coordination) the lack of cooperation between the Fisheries Service and community representatives, namely HNSI. External constraints (the occurrence of the monetary crisis) and the lack of public awareness of the objectives of the program. Keywords: Strategy of the Department of Fisheries, Distribution of Aid to Fishermen